Investigation of in vitro and in vivo Pursuits of Laurus nobilis Extract on Acetic Acid-induced Ulcerative Colitis in Wistar Rats - Al-Omran, Suliman Abdullah; Chinnikrishnaiah, Virdala; Ganesh, Vakkalagadda Siva; Goudanavar, Prakash; Naveen, Nimbagal Raghavendra; Fattepur, Santosh; Basavarajappa, Girish Meravanige; Shiroorkar, Predeepkumar Narayanappa; Telsang, Mallikarjun; Nagaraja, Sreeharsha (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: The ethanolic extract of Laurus nobilis possesses an anti-inflammatory effect, which will protect against acetic acid-induced Ulcerative colitis by inhibiting endogenous free radicals. Objectives: The work has been undertaken to explore the efficacy and safety of ethanolic leaf extract of Laurus nobilis in treating acetic acid-induced Ulcerative colitis by estimating the biochemical, physical parameters, and histopathological studies. Materials and Methods: The plant powder of L. nobilis was extracted using 70% ethanol, and a phytochemical investigation was performed. Male and Female Wistar albino rats were divided into six groups and pretreated with saline, saline followed by ulcer induction, two doses of extracts (100mg/kg and 200mg/kg b.w), and sulfasalazine (one day) followed by ulcer induction and one low dose extract treatment without inducing ulcer. Results: The phytochemical investigation of the extract confirms the presence of flavonoids. The biochemical estimations showed increased SOD, CAT, and GSH and decreased levels of TBARS in extract-treated groups compared to the acetic acid-induced group. The physical parameters like Crypt abscesses, gross mucosal inflammation, wet weight of the colon, diarrhea, and activity score have also shown better results in extract-treated groups showing a protective effect. Histopathological results further confirmed the therapeutic effect of the extract. Conclusion: The protective effect of ethanolic leaf extract of Laurus nobilis has been proved. The therapeutic effect was mainly due to flavonoids, and the low-dose extract was more potent than the high-dose extract.
Keywords: Laurus nobilis; Ulcerative Colitis; Anti-oxidant; Histological Studies; Ethanolic Extract